Measuring of the Yield and Risk of Emerging Markets and Developed Stock Markets - Radim Gottwald (Littera Scripta, 2013)
Financial analysts have recently paid more attention to so-called emerging markets that are slowly reaching the level of developed stock markets. The objective of this paper is to evaluate the level of yields and risk attributed to developed stock markets (USA, United Kingdom and Germany) and to emerging markets (Brazil is South America, Mexico in Central America, Hong Kong in Asia and Australia). These levels are set separately for the periods from 30 September 2004 to 30 September 2008 and from 30 September 2008 to 30 September 2012. The author compares the changes in levels between both periods and also development of the level of yields and risk within whole period of 12 months periodicity. The macroeconomic situation of these countries during selected period is monitored by means of GDP growth. The values of the stock indices are taken from major stock exchanges in these countries and bond yields are also used. Different standard deviations from the yield of the stock index, variation coefficients and Sharpe ratios are calculated. The author investigates to what extent it is true that higher yields can be achieved on emerging markets, but at the expense of a higher risk than on developed stock markets. Based on founded results it is clear that higher yields can be achieved on emerging markets at the expense of higher risk than on developed ones, but not in every case.